Sistemática para auxiliar as pequenas empresas industriais da cidade de São Carlos na identificação e análise dos impactos ambientais gerados durante o processo produtivo. - Zambrano, Tatiane Fernandes (Universidade Federal de São Carlos, 2004)
The aim of this study is to propose a method to help the small enterprises in the city of São Carlos to identify and analyze the environmental impact caused during their production processes. Six case studies were done in small enterprises of metal, textile, food, plastic, diagnosis kits sectors and in a marble and granite supplier. It was possible to conclude that: a) The method to identify and analyze environmental impact consists in a set of actions that the small enterprises can adopt to start to understand the environmental damage that their process or the incorrect discharge of their solid and liquid rejects will cause. b) With respect to case studies, it wasn t observed any environmental concern from the enterprises. The actions that these enterprises took to minimize the environmental impact of their process were motivated by: the concern to meet the requirements of inspection and financial return. c) The studies enterprises don t believe that the environmental system is important to their survival and the main difficult for these enterprises to adapt, environmentally speaking, is financial. In addition, the implementation of a system is not part of their strategy.
Keywords: Administração da produção; FMEA; Impacto ambiental; Gestão ambiental; Pequenas e médias empresas; Environmental management; Environmental impact; FMEA; Small enterprises; ENGENHARIAS::ENGENHARIA DE PRODUCAO